Exploring Drivers of Sellers’ Intention to Continue OCOP Agricultural Sales on Digital Platforms - Giang, Nguyen Thi Phuong; Duy, Nguyen Binh Phuong; Huyen, Nguyen Thi Thanh; Hang, Huynh Pham Thuy; Thu, Tran Vo Minh; Tien, Dang Tran Y.; Vang, Nguyen Van; Tan, Thai Dong (International Review of Management and Marketing, 2025)
The digital economy is becoming indispensable in promoting trade in OCOP (One Commune One Product) agricultural products in Vietnam. The emergence of digital platforms is increasingly diverse. Consumers can search on digital platforms to choose and buy when they need anything. This convenience is available in the central areas and has gradually spread to all provinces and cities with farmers. The study aims to build a model and evaluate the factors affecting the intention to continue selling OCOP agricultural products on the digital platform. The research focuses on the following factors: safety, compatibility, usefulness, ease of use, information technology knowledge, satisfaction, and intention to continue. The study uses quantitative and qualitative research methods. The author has surveyed 251 enterprises selling OCOP agricultural products nationwide. After collecting the answers, the data is analyzed using SPSS software, SmartPLS. From that data, propose solutions to help digital platforms review and improve service quality. Strengthen the intention of sellers to continue using agricultural products on digital platforms. At the same time, come up with strategies to help sellers understand digital platforms. In addition, this also increases sales efficiency when participating in selling agricultural products in the Vietnamese market in general and the international market in particular.